Effects of public funding on the commercial diffusion of on-site hydrogen production technology: A system dynamics perspective - Gao, Jiayang; Zhang, Tao (Technological forecasting & social change, 2022)
•We use a system dynamics model to study on-site hydrogen technology adoption.•We use market data of hydrogen development in California for modelling.•Moderate public funding boosts on-site hydrogen production technology development.•We provide policy implications for building hydrogen infrastructure. As the prospect of the fuel cell electric vehicle (FCEV) market is uncertain, the effects of government subsidies on the commercial diffusion of hydrogen production infrastructure will need to be effectively evaluated to help policymakers decide how they should financially support the development of future hydrogen technologies. Currently, there is a high intermediate cost in the supply chain of centralized hydrogen production. Decentralized on-site hydrogen production technology is an effective alternative method that can guarantee the operation of hydrogen refueling stations and has been attracting more and more attention from the public. In this paper, which is based on market data from California, we build a system dynamics model to simulate the feedback mechanism of the effects of public funding on the commercial diffusion of on-site hydrogen production technology. The insights derived from the simulation of our system dynamics model suggest that: (1) moderate public funding can help establish the scale of application of on-site hydrogen production technology in the early stages of market development and also provide buffer time for technology upgrading; (2) the adoption of large on-site hydrogen refueling stations is a feasible approach to shorten the standstill period; and (3) excess levels and periods of subsidies would stagnate the growth of supply and demand. We conclude with a discussion about the relevant policy implications from these findings.